A case study of distress mechanism(s) in a concrete structure foundation in the saturated zone and above the saturated zone. (26th October 2021) - Beyene, Mengesha; Meininger, Richard
Abstract: In this case study, distress mechanism(s) of a concrete structure in the saturated and unsaturated zones of the foundation were investigated. This research was performed using a stereomicroscope, polarised light microscopy (PLM), and a limited study using a scanning electron microscope (SEM) with backscattered electron (BSE). Results of this study showed that concrete cores extracted from both the saturated and unsaturated zones of the foundation exhibited severe to moderate concrete distress, but the cause of the distress/cracking in the concrete was not related to Alkali‐Carbonate Reaction (ACR) as was initially suspected. While the damage to the concrete extracted from the structure above the saturated zone of the foundation was caused by a combination of Alkali‐Silica Reaction (ASR) and freeze‐thaw deterioration, concrete distress in the saturated zone of the foundation was caused primarily by ASR of shale particles in the natural sand fine aggregate. The sand also contained traces of chert particles with ASR. Limited ASR was seen in the crushed gravel coarse aggregate siliceous limestone, dolomitic limestone, and chert particles. Results of this case study showed that siliceous shale particles in the fine aggregate caused detrimental ASR damage to the concrete, and thus caution needs to be exercised when aggregate containing shale is used in concrete.